PENENTUAN SISTEM ANTRIAN KENDARAAN UNTUK MENENTUKAN EFEKTIVITAS JUMLAH GARDU PADA GERBANG TOL PT. JASA MARGA (PERSERO) TBK (STUDI KASUS GERBANG TOL CIBUBUR1) - Suryobuwono, Abdullah Ade; R, Marthaleina; Lestari, Putri; Mahersa, Raka Putra; Musyaffa, Arya Yudhistira (Jurnal Sistem Transportasi & Logistik, 2021)
The aims of this study are: (1) To determine the queuing system at the Cibubur 1 toll gate; (2) to determine the effectiveness of the toll booth queues available at the Cibubur 1 toll gate; and (3) to find out the strategy for improving the service of the toll booth at the Cibubur toll gate1. The data used is secondary data obtained from PT. JASA MARGA (Persero) Tbk. In this study, the queuing system method is used, the data used is from August - October 2019, the time period is divided into 3 time zones each day which includes morning (06.00-10.59), afternoon (11.00-15.59) and afternoon (16.00-5.00pm). 20.59), and each time zone is calculated every 5 hours. The results of this study indicate that the highest average arrival rate is in August reaching 9,847 vehicles, while the highest average vehicle hourly rate occurs in the afternoon, namely at 16.00-20.59 in August - October. In improving the service strategy, the research results can be applied as follows, making arrangements for the composition of traffic, improving the road network, regulating drivers and developing infrastructure services.